The Role of Logistics in Supporting Domestic Economy and Industrial Growth: A Literature Review Study - Susanto, Primadi Candra; Perwitasari, Erni Pratiwi; Lermatan, Esterlinus Edwin; Silalahi, Tiur Mery B (Siber Journal of Transportation and Logistics, 2024)
This study aims to explore the crucial role of the logistics sector in promoting economic growth and the advancement of national industries through a literature review approach. Amid globalization and increasing market competition, the success of industrial development heavily depends on the effectiveness and efficiency of logistics systems. This review examines various literature sources discussing the contribution of logistics to supply chain optimization, distribution efficiency, cost reduction, and its impact on industrial productivity. The findings reveal that an integrated logistics system, supported by strong infrastructure, can enhance the competitiveness of domestic industries while expanding market reach. Logistics also acts as a vital connector between producers, consumers, and international markets, directly contributing to national economic growth. The study recommends strengthening national logistics policies, improving human resource capacity in logistics, and accelerating the development of transportation infrastructure and technology to support a sustainable and competitive logistics system.